People can understand descriptions of motion without activating visual motion brain regions - Dravida, Swethasri; Saxe, Rebecca; Bedny, Marina (Frontiers in Psychology, 2013)
What is the relationship between our perceptual and linguistic neural representations of the same event? We approached this question by asking whether visual perception of motion and understanding linguistic depictions of motion rely on the same neural architecture. The same group of participants took part in two language tasks and one visual task. In task 1, participants made semantic similarity judgments with high motion (e.g., “to bounce”) and low motion (e.g., “to look”) words. In task 2, participants made plausibility judgments for passages describing movement (“A centaur hurled a spear … ”) or cognitive events (“A gentleman loved cheese …”). Task 3 was a visual motion localizer in which participants viewed animations of point-light walkers, randomly moving dots, and stationary dots changing in luminance. Based on the visual motion localizer we identified classic visual motion areas of the temporal (MT/MST and STS) and parietal cortex (inferior and superior parietal lobules). We find that these visual cortical areas are largely distinct from neural responses to linguistic depictions of motion. Motion words did not activate any part of the visual motion system. Motion passages produced a small response in the right superior parietal lobule, but none of the temporal motion regions. These results suggest that (1) as compared to words, rich language stimuli such as passages are more likely to evoke mental imagery and more likely to affect perceptual circuits and (2) effects of language on the visual system are more likely in secondary perceptual areas as compared to early sensory areas. We conclude that language and visual perception constitute distinct but interacting systems.